Webbed penis: A new classification - El-Koutby Montasser; El Gohary Mohamed Amin (Wolters Kluwer Medknow Publications, 2010)
Aim: To introduce a new classification for the congenital anomaly of webbed penis and suggest an operative technique that can be planned according to the severity of webbing. Materials and Methods: A prospective study was conducted in two pediatric surgical units in Egypt and UAE on babies who were referred for circumcision. A preplanned written protocol was designed before commencing the study. Results: A total of 5,881 babies aged from 1 day to 6 months were seen in two pediatric surgical units. The webbed penis is broadly classified into primary and secondary types. The primary is further subdivided into simple and compound. Conclusion : We believe that the new classification will serve as a baseline for the anatomical variants and help to streamline the operative procedure accordingly.